Qualitative and Quantitative Analysis of Green Supply Chain Management (GSCM) Literature From 2000 to 2015 - Saeid Jafarzadeh-Ghoushchi (International Journal of Supply Chain Management, 2018)
In the past several decades, Green Supply Chain Management (GSCM) has been rapidly evolving in academia and industry and investigation in all countries and nation growing dramatically. The significant impact of GSCM is visible by the rate of academic publications in recent years. With the increased attention paid to environmental aspects of green supply chain management, finding new directions by critically evaluating the research and identifying future directions becomes important in advancing knowledge for the field. Both Qualitative and quantitative are applied to examine global scientific production of green supply chain management in Science Citation Index (SCI-Index) and Social Sciences Citation Index (SSCI-Index) documents to develop a viable green supply chain study. The analytical results of this study illustrate the study evolution over time and eventually provide a systematic mapping of the field that helps to identify of research interests and potential directions for future research.